Key determinants of health and wellbeing of dental nurses: a rapid review of over two decades of research - Nana Adwoa Opoku-Ansah; Jennifer E. Gallagher; Victoria Niven (BDJ Open)
Abstract Aim To review the literature on the key determinants of health and well-being amongst dental nurses. Method A rapid review of the literature using Khangura’s approach across seven health and social science databases was conducted (2002 to 2023), through OVID and the Cochrane Library, professional and health system databases—informed by past research exploring the health and well-being of dental professionals. A two-stage review process was implemented where records were screened by the primary researcher, with a second researcher independently reviewing 10% of the papers according to agreed inclusion and exclusion criteria. Data extraction and qualitative synthesis of the included studies were conducted, and quality was assessed using a Mixed Methods Appraisal Tool. Results Out of 4,450 identified papers, 44 underwent full-text screening and 37 studies were included for analysis. Four studies were of high quality, 13 moderate-high, 14 moderate-low and six low-quality. The overall health and well-being of dental nurses was variable and the determinants influencing well-being were grouped into micro-, meso- and macro-level factors with evidence across the three domains with the most frequently identified determinant being workplace characteristics. Dental nurses with extended duties had higher job satisfaction. There was evidence that during the COVID-19 pandemic, there were increased levels of anxiety, stress, burnout and isolation among dental nurses. Conclusion The body of research suggests that dental nurses’ health and well-being determinants are comparable to those of other dental professionals. Dental nurses in different countries had similar determinants. It is important to recognise and improve the determinants of dental nurses’ health and well-being to support retention within the profession. Organisational and policy changes may help improve the well-being of dental nurses. Further investigation into dental nurses’ health and well-being over time is needed.